Unraveling the Influence: Exploring the Role of User Generated Content Along the Customer Journey and Understanding Its Relevance for Research and Practice - Schröder, Nadine; Schultz, Carsten D.; Paetz, Friederike; Grzadziel, Alicja; Clegg, Melanie (Schmalenbach Journal of Business Research)
This article addresses the role of user-generated content (UGC) across the different stages of the customer journey and the decision process. Various types of UGC, such as online reviews and social media posts, significantly affect how customers engage with brands and make purchasing decisions. Based on a structured review of 342 research articles dealing with UGC, we develop a comprehensive framework that categorizes existing research findings across the three stages of the customer journey—prepurchase, purchase, and postpurchase—along six key UGC dimensions: “UGC characteristics”, “product characteristics”, “writer characteristics”, “consumer characteristics”, “interaction characteristics”, and “other characteristics”. Our analysis reveals that most research has focused on how “UGC characteristics” impact the prepurchase stage, while the purchase and postpurchase stages, as well as certain product types, remain underexplored. Based on our findings, we address avenues for future research and provide actional insights for companies on encouraging content creation. The public accessibility of UGC necessitates that companies monitor it and think about possible response strategies. This is particularly relevant if the content develops in a negative way. Finally, monitoring the content proactively allows companies to gain additional customer information and possibly generate ideas for future product or service innovations.